2012
DOI: 10.1249/mss.0b013e318236a3d2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the Human Hamstring Muscles during Sprinting

Abstract: As peak musculotendon force and strain for BF, ST, and SM occurred around the same time during terminal swing, it is suggested that this period in the stride cycle may be when the biarticular hamstrings are at greatest injury risk. On this basis, hamstring injury prevention or rehabilitation programs should preferentially target strengthening exercises that involve eccentric contractions performed with high loads at longer musculotendon lengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
292
1
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(325 citation statements)
references
References 45 publications
12
292
1
20
Order By: Relevance
“…Assimetria é entendida como um favorecimento de um membro, inferior ou superior, em detrimento do outro (27) para desempenhar ações motoras complexas e pode estar relacionada à redução do desempenho motor (7,13) , embora seja uma questão ainda incipiente, e ao aumento do risco de lesões musculares nos membros inferiores em jogadores de futebol (10,26) e de esportistas colegiais (5) . Em um estudo com jogadores de futebol, os resultados mostraram que jogadores de futebol com maior assimetria de força nos membros inferiores (8 ± 1%; p < .01) apresentaram menor precisão na técnica do chute por causa da capacidade reduzida da manutenção do equilíbrio (13) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Assimetria é entendida como um favorecimento de um membro, inferior ou superior, em detrimento do outro (27) para desempenhar ações motoras complexas e pode estar relacionada à redução do desempenho motor (7,13) , embora seja uma questão ainda incipiente, e ao aumento do risco de lesões musculares nos membros inferiores em jogadores de futebol (10,26) e de esportistas colegiais (5) . Em um estudo com jogadores de futebol, os resultados mostraram que jogadores de futebol com maior assimetria de força nos membros inferiores (8 ± 1%; p < .01) apresentaram menor precisão na técnica do chute por causa da capacidade reduzida da manutenção do equilíbrio (13) .…”
Section: Introductionunclassified
“…A assimetria de força pode ser mensurada por diferentes métodos tais como testes isocinéticos (10,15) , saltos horizontais e verticais e variações desses com ou sem determinação das forças de reação de solo (11,20) , testes isométricos de extensão do joelho (26,22) , testes de uma repetição máxima (21) e agachamento realizado em plataforma de força (22) . Apesar dos diversos métodos disponíveis, tanto o teste isocinético quanto os testes em plataforma de força, muitas vezes, são inacessíveis às equipes esportivas, principalmente nas categorias de base de futebol, assim, os saltos horizontais (salto horizontal monopodal) e suas variações têm sido frequentemente propostos como um método confiável (CCI = 0.95 e 0.80, membro inferior dominante e não dominante, respectivamente) (19) para a identificação da assimetria de força requerendo mínima demanda financeira, pouco tempo para sua administração e facilidade de interpretação dos resultados (24) .…”
Section: Introductionunclassified
“…However, Schache and colleagues (2012) suggest that the biomechanical load and therefore the contribution of each of these muscles during this phase are different. The authors found BFLongHead exhibits the largest peak strain, ST displays the greatest lengthening velocity, and SM produces the highest peak force, generates the most power and performs the largest amount of work during the terminal swing phase of running (Schache et al, 2012).…”
Section: Mechanism(s) Of Hamstring Strain Injurymentioning
confidence: 99%
“…Some argue that HSI is most likely to occur during the terminal swing phase of running (Brooks et al, 2005a;Ekstrand et al, 2011a;Woods et al, 2002;Yu et al, 2008) where high stress (Schache, Dorn, Blanch, Brown, & Pandy, 2012) and moderate strain (Thelen, Chumanov, Best, Swanson, & Heiderscheit, 2005) is placed on the muscle. There are only two case studies in which HSI during running has been observed, and both studies suggest that HSI occurred when the hamstrings were actively lengthening during the terminal swing phase of running Schache, Wrigley, Baker, & Pandy, 2009).…”
Section: Mechanism(s) Of Hamstring Strain Injurymentioning
confidence: 99%
See 1 more Smart Citation